Ichthyological inventory of Lower Dibang Valley, Arunachal Pradesh, India - Gurumayum, Shantabala Devi (Journal of the Inland Fisheries Society of India, 2021)
A total of 73 fish species were identified belonging to 8 orders, 20 families and 47 genera from different natural aquatic resources of Lower Dibang valley of Arunachal Pradesh. Conservation status of the fishes were worked out following the IUCN Red List Status and observed the presence of 2 Endangered species, 5 Near Threaten species along with 4 Vulnerable and 4 Data Deficient species. Report of getting three exotic viz., Salmo trutta, Oreochromis niloticus and Cyprinus carpio from the natural water bodies of the district is an ecological concern. Key words Dibang river, fish, conservation status, endangered, exotic